RANCANG BANGUN ALAT PERMAINAN EDUKASI ANAK 4-6 TAHUN BERBASIS ANIMASI 3D DENGAN PENDEKATAN VISUAL ALAT TRANSPORTASI TRADISIONAL DAN MODERN - Aswar; Agussalim Djirong; Faisal Erlangga Makawi (SEMINAR NASIONAL DIES NATALIS 62, 2023)
It is well known that early childhood is the initial stage that requires more intensive attention, because it is at this age that the fundamental educational process begins to build the basic framework of children's knowledge, attitudes and skills. Order in the educational process at this early age becomes the main competency to determine the sustainability of children's education. Educational game tools based on 3-dimensional animation with a visual approach to traditional and modern transportation are media facilities by integrating digital technology that has benefits and educational value for children, which previously used simulation media in the form of pazzel which was played conventionally. The utilization of this game tool can be through children's learning activities by playing digital simulations through the form of transportation equipment, intended to stimulate all aspects of religious morals, physical motor, cognitive, language, social emotional and art. The purpose of this research is to find out the design form of educational game tools and the stages in designing 3-dimensional animation through the form of traditional and modern transportation visual tools. The method used is R&D with a design thinking approach. The result of this research is the creation of a 3-dimensional animation-based educational game tool with traditional and modern visual transportation tools.